ON WORD, LAUGH AND POWER (Proceedings of Southern Federal University. Philology, 2013)
Strukova T.Keywords: author, interpretation of the text, the author’s intentions, the horizon of the text, the horizon of the reader’s expectation, a model reader.The problems of interpretation of the text as a multivalued phenomenon are considered in this article. The interpretation of the text has important limiting factors: the author’s intentions, the horizon of the text, the horizon of a reader, a model reader.